Effects of short days on stem elongation in some indeterminate dry bean cultivars adapted to the tropics - Masaya, P.M.; White, Jeffrey W. (International Center for Tropical Agriculture, 1985)
The effect of 2 daylength treatments (11 and 15 h) on stem elongation was determined in 5 indeterminate bean cv. (G 17650, G 2997, DOR 44, G 5475, and JU 80-11) under growth chamber conditions. Under the short day length, G 17650, a viny indeterminate var. showed the longest stem under all conditions. G 2997 and DOR 44, currently used in Central America in relay cropping, showed the highest degree of stem elongation, under short days compared with long days. This fact suggests that this trait is beneficial for relay cropping. (CIAT)